Un Éros de celluloïd : l’érotisation cinématographique de Paris (1945-1975) - Frédéric Hervé (Genre, Sexualité et Société)
How did motion pictures reinforce Paris' hedonistic and erotic reputation? The question is answered through a corpus of films whose titles include the city itself, one of its neighborhoods, or one of its entertainment venues. They are short or feature films – including fiction, documentary, and even hybrids – that mainly proliferated during the 1950’s. These films feature erotically-charged female characters and contribute to a gender-biased depiction of their subjects. Neighborhoods and entertainment venues, as well as other parts of the city, are not simply backdrops for the films, but their subjects as well. For the most part, the depictions in these films had been previously constructed by other media. Consequently, in translating clichés about the city to film, directors had to break ground in terms of form more than content. Moreover, they also had to abide by the norms of acceptability established by the public authorities monitoring representations of the capital.